2020
DOI: 10.1080/07391102.2020.1776155
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics studies of dog prion protein wild-type and its D159N mutant

Abstract: Prion diseases (e.g. 'mad cow' disease in cattle, chronic wasting disease in deer and elk, Creutzfeldt-Jakob disease in humans) have been a major public health concern affecting humans and almost all animals. However, dogs are strongly resistant to prion diseases. Recently, through transgenic techniques, it was reported that the single (surface) residue D159 is sufficient to confer protection against protein conformational change and pathogenesis, thus provides conformational stability for dog prion protein. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Because dogs are resistant to prion infection, partly because of the presence of Asp159 in their PrP ( 26 , 27 , 28 , 29 , 30 , 33 , 34 , 35 ), and Asp159 suppresses the toxicity of mouse PrP in Drosophila ( 27 ), we chose to investigate the regulation mechanism of Asp159 on PrP C liquid-phase condensation. We used two mutations at codon 159, bacterial-purified N159D of human PrP C and D159N of dog PrP C , labeled by TAMRA (red fluorescence) and incubated with 1× PBS (pH 7.4) containing 10% (w/v) PEG 8000 on ice.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Because dogs are resistant to prion infection, partly because of the presence of Asp159 in their PrP ( 26 , 27 , 28 , 29 , 30 , 33 , 34 , 35 ), and Asp159 suppresses the toxicity of mouse PrP in Drosophila ( 27 ), we chose to investigate the regulation mechanism of Asp159 on PrP C liquid-phase condensation. We used two mutations at codon 159, bacterial-purified N159D of human PrP C and D159N of dog PrP C , labeled by TAMRA (red fluorescence) and incubated with 1× PBS (pH 7.4) containing 10% (w/v) PEG 8000 on ice.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, several in vitro and in vivo studies have demonstrated that Asp159 from the dog PrP plays a critical role in encoding higher structural stability of PrP in prion-resistant canids ( 26 , 27 , 28 , 29 , 30 , 33 , 34 , 35 ). Because Arg177 and Asp159 cause unique charge distribution patterns on the front and back sides of dog PrP C , it has generally been thought that these two unique amino acid residues might be responsible for the prion resistance of canids ( 27 , 28 , 29 , 52 , 53 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations